Can Capitalists Afford Recovery? A 2018 Update and a Closer Look - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2018)
This research note starts by showing that, for much of the postwar period, U.S. unemployment to has been a highly reliable leading indicator for the capitalist share of domestic income three years later, and then assesses whether this relationship still holds.
Keywords: P16; E24; D3; 330; crisis; income distribution; power; sabotage; unemployment